2022
DOI: 10.21203/rs.3.rs-1993546/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Medication adherence and cognitive performance in schizophrenia-spectrum and bipolar disorder: results from the PsyCourse Study

Abstract: Existing guidelines recommend psychopharmacological treatment for the management of schizophrenia and bipolar disorder as part of holistic treatment concepts. About half of patients do not take their medication regularly, although treatment adherence can prevent exacerbations and re-hospitalizations. To date, the relationship of medication adherence and cognitive performance is understudied. Therefore, this study investigated the relationship between medication adherence and cognitive performance by analyzing … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…Interestingly, a longitudinal study [77] investigating the e↵ect of anti-psychotic treatment discontinuation showed that those individuals who did not remain on their medication after a 3.5 year follow up had improved significantly more than those who stayed on their medication even when controlling for symptom severity and cognitive scores at baseline. General non-adherence of medication use, however, does not have the same positive e↵ect on cognition [79]. Especially, anticholinergic medication has been associated with a high cognitive burden [78], which is being supported by our results.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, a longitudinal study [77] investigating the e↵ect of anti-psychotic treatment discontinuation showed that those individuals who did not remain on their medication after a 3.5 year follow up had improved significantly more than those who stayed on their medication even when controlling for symptom severity and cognitive scores at baseline. General non-adherence of medication use, however, does not have the same positive e↵ect on cognition [79]. Especially, anticholinergic medication has been associated with a high cognitive burden [78], which is being supported by our results.…”
Section: Discussionsupporting
confidence: 81%
“…Cognitive impairment is a major contributor to functional disability in severe mental illnesses (SMI), including schizophrenia (SZ) and bipolar (BD) spectrum disorders (Green, 2006;Wingo et al, 2009). Existing pharmacological treatments have little to no effect on cognitive symptoms (Nielsen et al, 2015;Senner et al, 2023), which may precede illness onset (Dickson et al, 2012;Sheffield et al, 2018) and persist throughout the illness course (Bonner-Jackson et al, 2010;Flaaten et al, 2023Flaaten et al, , 2022. While several pathophysiological mechanisms may be involved (McCutcheon et al, 2023), inflammatory and immunological dysregulation observed in SMI have emerged as a possible contributor to cognitive impairment (Kogan et al, 2020;Misiak et al, 2018;Morozova et al, 2022;Rosenblat et al, 2015).…”
Section: Introductionmentioning
confidence: 99%